Hyperglycemia is associated with cardiac complications in elderly nondiabetic patients receiving total parenteral nutrition - Ma, Jinling (Medicine (Baltimore), 2018)
Adverse outcomes have been associated with hyperglycemia in patients receiving total parenteral nutrition (TPN). The relationship may be characteristic in elderly patients. However, limited data are available about the relationship between TPN-related hyperglycemia and cardiac adverse outcome in elderly patients without previously known diabetes. This study aims to identify whether there is an association between hyperglycemia and 45-day cardiac adverse outcomes in critically and noncritically ill elderly nondiabetic patients receiving TPN. Outcome measures of 45-day cardiac complications after receiving TPN were recorded from a retrospective review of 1517 medical and surgical elderly patients. The mean glucose levels were significantly higher in patients with cardiac complications than in patients without cardiac complications (P < .001). In multivariate logistic regression analysis adjusting for age, gender, comorbidities, and medications, higher mean blood glucose levels were independently associated with increased 45-day cardiac complications (odds ratio, 1.62; 95% confidence interval, 1.453–1.816; P < .001). Furthermore, Kaplan–Meier event-free survival curves demonstrated that patients with mean blood glucose level ≥11.1 mmol/L had worse cardiac complications event-free survival compared with those mean blood glucose level <11.1 mmol/L during 45 days after receiving TPN. This study showed that TPN-induced hyperglycemia was associated with increased risk of cardiac complications in both critically and noncritically ill elderly patients without a history of diabetes.